2020
DOI: 10.3892/or.2020.7669
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor produced by cancer‑associated fibroblasts correlates with poor prognosis in epithelioid malignant pleural mesothelioma

Abstract: Malignant mesothelioma is an aggressive neoplasm for which effective treatments are lacking. We often encounter mesothelioma cases with a profound desmoplastic reaction, suggesting the involvement of cancer-associated fibroblasts (CAFs) in mesothelioma progression. While the roles of CAFs have been extensively studied in other tumors and have led to the view that the cancer stroma contains heterogeneous populations of CAFs, their roles in mesothelioma remain unknown. We previously showed that connective tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…CAFs are able to remodel ECM by the production of several ECM-related proteins (e.g., integrins) that mediate the crosstalk with tumor cells and promote local invasion and metastatic spread [ 64 ]. These spindle-like cells are also found in mesothelioma tissue, associated with pro-tumor functions, such as stromal remodeling and tumor invasion, and are correlated with poor prognosis [ 65 ]. Ohara et al proposed a mechanism by which fibroblasts participate to pleural fibrosis in the early mesothelioma phases in response to ROS production by frustrated macrophages.…”
Section: Mesothelioma Microenvironment Crosstalk: Molecular Mechanismsmentioning
confidence: 99%
“…CAFs are able to remodel ECM by the production of several ECM-related proteins (e.g., integrins) that mediate the crosstalk with tumor cells and promote local invasion and metastatic spread [ 64 ]. These spindle-like cells are also found in mesothelioma tissue, associated with pro-tumor functions, such as stromal remodeling and tumor invasion, and are correlated with poor prognosis [ 65 ]. Ohara et al proposed a mechanism by which fibroblasts participate to pleural fibrosis in the early mesothelioma phases in response to ROS production by frustrated macrophages.…”
Section: Mesothelioma Microenvironment Crosstalk: Molecular Mechanismsmentioning
confidence: 99%
“…Although ISLR was discovered as early as 1997, it has not been fully studied in tumors. Some studies have reported that ISLR plays an important role in tumor progression in CAFs, such as colorectal cancer, pancreatic cancer, and malignant pleural stromal tumors [7,23,24]. This means that ISLR may play a role in the TME, which is one of the reasons why we conducted this research on the role of ISLR in pan-cancer and tumor immunity.…”
Section: Discussionmentioning
confidence: 94%
“…Using surgical specimens of epithelioid MPM, the authors evaluated the clinicopathological significance of αSMA expression, the most widely used marker of CAFs, the expression of CTGF, and the extent of fibrosis by immunohistochemistry. They showed that the expression of αSMA and CTGF in CAFs correlated with poor prognosis in epithelioid subtype MESO patients 40 .…”
Section: Discussionmentioning
confidence: 99%